On some merits of the Israeli judgment on targeted killings - Cassese, Antonio (Journal of international criminal justice, 2007)
The recent judgment by the Israeli Supreme Court on targeted killings is a landmark decision in many respects. Its main merit lies in trying to give precision to, and therefore make concretely applicable by the belligerents, some loose standards of international humanitarian law on the conduct of hostilities. In particular, the judgment is significant because (i) it concluded that the issue of targeted killings did not amount to a non-justiciable question, (ii) it suggested a novel and imaginative way of narrowing down the vague scope of imprecise international rules on methods of combat, and in addition (iii) it set out a range of measures that belligerents must take both before and after armed attacks against civilians participating in hostilities, so as to avoid damage to innocent civilians as far as possible. The measures authoritatively suggested in the judgment may serve both to turn some unclear international rules into workable standards of conduct, and also to open the way to the possible prosecution of individuals (superiors and subordinates) who do not comply with such standards